Rancang Bangun Aplikasi Rekapitulasi Obat dengan Menerapkan Tanda Tangan Digital - Aulia Tri Rahmawati; Raden Budiarto Hadiprakoso (ULTIMA InfoSys, 2020)
The current condition experienced by the XYZ Polyclinic is that there is no application built to simplify the service process contained in the polyclinic so that all service processes are still manual. An example is the calculation of the number of drugs that are in and out of use. This calculation takes a long time, is prone to errors in accounting, and consumes many papers. To solve this problem, we develop an application to recap drugs. The drug recapitulation application is based on a website with the WebML method using the CodeIgniter framework and MySQL database. The application produces the result in the form of a PDF file of the drug recapitulation report per month and day. As a security feature, the monthly drug recapitulation report results include a digital signature as proof of authentication, integrity, and anti-denial. The application built has been tested using web testing methods and user acceptance testing to be applied.